2016
DOI: 10.1161/hypertensionaha.116.07562
|View full text |Cite
|
Sign up to set email alerts
|

Novel Protective Role for Ubiquitin-Specific Protease 18 in Pathological Cardiac Remodeling

Abstract: Abstract-Ubiquitin-specific protease 18 (USP18), a USP family member, is involved in antiviral activity and cancer inhibition. Although USP18 is expressed in heart, the role of USP18 in the heart and in cardiac diseases remains unknown. Here, we show that USP18 expression is elevated in both human dilated hearts and hypertrophic murine models. Cardiomyocyte-specific overexpression of USP18 in mice significantly blunted cardiac remodeling as evidenced by mitigated myocardial hypertrophy, fibrosis, ventricular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…An Alexa Fluor 488 conjugate of WGA was used to visualize cardiomyocyte boundaries, and the size of cardiomyocytes was found to increase with age (Fig 7), consistent with previous reports [1]. This suggested that hypertrophy was an alternative growth method when cardiomyocytes exit proliferation [18]. …”
Section: Resultssupporting
confidence: 87%
“…An Alexa Fluor 488 conjugate of WGA was used to visualize cardiomyocyte boundaries, and the size of cardiomyocytes was found to increase with age (Fig 7), consistent with previous reports [1]. This suggested that hypertrophy was an alternative growth method when cardiomyocytes exit proliferation [18]. …”
Section: Resultssupporting
confidence: 87%
“…In hearts of patients with dilated cardiomyopathy, USP18 expression was significantly higher than in hearts from healthy donors. Moreover, in murine hearts exposed to increased afterload, augmented expression of USP18 in cardiomyocytes was related to less pronounced myocardial fibrosis, reduced left ventricular wall hypertrophy and delayed onset of heart failure (Ying et al, 2016). In contrast, USP18deficient mice presented advanced cardiac remodelling (Ying et al, 2016).…”
Section: Cardiac Remodellingmentioning
confidence: 98%
“…Ying and others (Ying et al, 2016) had shed a new light on activity of USP18 and extended its action to the cardiovascular system. Their study demonstrated that USP18 inhibits cardiac remodelling and protects from the development of heart failure.…”
Section: Cardiac Remodellingmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental study, the overexpression of A20 attenuated the hypertrophic stimulant such as phenylephrine-induced development of pathological hypertrophy. 92 97 A molecular study found that USP18 inactivates TAK1 by deubiquitinating K63-linked polyubiquitination and it subsequently suppresses the downstream NF-jB and JNK1/2 signalling pathways, which plays critical role in NAFLD progression. 98 USP14 also contributes to suppress the development of cardiac hypertrophy by increasing phosphorylation of GSK-3b (Table 2).…”
mentioning
confidence: 99%